Dionysiac. - Criqui, Jean-Pierre; Hiddleston, Anna; Macel, Christine; Pacquement, Alfred; Racine, Bruno; Stiegler, Barbara; Exhibition. Dionysiac. Centre Pompidou Paris. 2005-02-16. 2005-05-09 (Paris : Centre Pompidou Paris, 2005)
Gelatin ; Bock, John ; Tyson, Keith ; Hyber, Fabrice ; Geers, Kendell ; Rhoades, Jason ; McCarthy, Paul ; Kersels, Martin ; Meese, Jonathan ; Farrell, Malachi ; Jackson, Richard ; Büchel, Christoph ; Cattelan, Maurizio ; Hirschhorn, Thomas
Abécédaire [48 p.]
Frans
boek